Combination of spraying based liquid phase microextraction and liquid chromatography-tandem mass spectrometry for the determination of colchicine at ultra-trace levels in artificial urine and serum samples - Kutlu, Rabia; Bodur, Suleyman; Gunkara, Omer Tahir; Bakirdere, Sezgin (ELSEVIER, 2024)
Colchicine is a primary choice for the treatment of acute gouty arthritis, but this pharmaceutical active substance has serious side effects. For this reason, a sensitive and accurate analytical method is required to quantify colchicine at trace levels in order to evaluate the side effects deeply. In this study, liquid chromatography-atmospheric pressure ionization-tandem mass spectrometry (LC-API-MS/MS) was firstly combined with spraying based fine droplet formation liquid phase microextraction (SFDF-LPME) to determine colchicine in artificial serum and urine samples at ultra-trace levels. The SFDF-LPME-LC-API-MS/MS parameters were elaborately optimized to reach low detection limits. Dynamic range, limit of detection (LOD) and limit of quantitation (LOD) of the SFDF-LPME-LC/MS/MS were recorded as 5.34 - 173.69 ng/kg, 1.67 ng/kg and 5.57 ng/kg, respectively. The detection power of LC-API-MS/MS system was enhanced by 106-fold when the LOD values of LC-API-MS/MS and SFDF-LPME-LC-API-MS/MS methods were compared to each other. After the evaluation of system analytical performance, recovery experiments were conducted with the spiked artificial serum and urine samples. Percent recovery results for the spiked artificial serum and urine samples were figured out to be 99.1 % - 108.6 % and 89.4 % - 114.8 % via external standard calibration method, respectively. Additionally, matrix-matching calibration strategy was applied to calculate the recovery results, which were recorded as 94.6 % - 101.3 % and 79.0 % - 106.8 %, for the spiked artificial serum and urine samples, respectively. The obtained acceptable recovery results via the applied two calibration strategies proved the applicability and accuracy of developed method for the determination of colchicine at ultra-trace levels.
Keywords: Artificial serum and urine; Colchicine; Spraying based fine droplet formation liquid; phase microextraction; Tandem mass spectrometry; GAS-CHROMATOGRAPHY; EXTRACTION; QUANTIFICATION; Chemistry